The determinants of core inflation in the Republic of Macedonia - Magdalena Petrovska; Misho Nikolov (Journal of Contemporary Economic and Business Issues, 2018)
We investigate the determinants of core inflation in Macedonia and show that the most important drivers of the cumulative core inflation in the post crisis period i.e. between 2010-16 relative to 2008-09 are underutilization of labor in the form of involuntary part-time employment and headline unemployment rate. Both indicators have contributed positively to cumulative core inflation since 2015 but headline unemployment rate much less so. The contribution of trend productivity growth has remained negligible. Sluggishness in core inflation faced against the background of relatively buoyant activity in the post-crisis period-has corresponded with slow pass through from declining unemployment rates to faster wage growth. We suggest that core inflation rates in Macedonia will likely remain low unless wage growth speeds-up beyond productivity growth more sustainably.
Keywords: E2; E24; C22; 330; Core inflation; unemployment; productivity; underemployment